Genetic characterization of three fertility genes in Egyptian sheep and goat breeds - OTHMAN, OTHMAN E; EL-KADER, HEBA A ABD; EL-RAHIM, ABEER H ABD; EL-MONEIM, OMAIMA M ABD; ALAM, SALLY S (The Indian Journal of Animal Sciences, 2018)
One of the effective approaches for genetic improvement of productivity traits in farm animals is markerassisted selection (MAS) depending on the genetic markers that are associated with superior productivity traits. The improvement of fertility trait is one of the main targets in small ruminant breeding programs. This work aimed to identify RFLPs and SNPs variations among three fertility genes in Egyptian sheep and goat breeds. RFLP analysis of the amplified fragments at 462-bp from exon 1 of GDF9 using HpaII endonuclease showed the presence of two genotypes GG and AG. Depending on the presence of the restriction site of TaqI endonuclease (T^CGA) in the 348-bp amplified fragment from exon 5 of GPR54 gene, the results showed the presence of two alleles, C and T with three genotypes, viz. CC, TT and CT. The PCR amplified fragments of 190-bp from FecB gene were digested with AvaII restriction enzyme and the results showed that all tested animals had the same homozygous non-carrier genotype (++). It was concluded that the identification of genetic structure and nucleotide sequences of GDF9, GPR54 and FecB genes is considered the first step towards the genetic improvements of fertility trait in Egyptian small ruminants where these genes are associated with different fertility traits parameter like ovulation rate, ovarian follicular development, puberty and litter size in small ruminant breeds.